COMPUTED TOMOGRAPHIC ASSESSMENT OF PULMONARY NODULE DENSITY AND DISTRIBUTION IN DOGS - Robert Cristian Purdoiu; Teodora Patrichi; Felix Daniel Lucaci; George Tudor; Radu Lăcătuș; Sorin Marian Mârza (Agricultura, 2025)
Abstract: Computed tomography (CT) is increasingly utilized in veterinary medicine for thoracic imaging due to its high sensitivity in detecting pulmonary nodules, far surpassing traditional radiography. Pulmonary nodules in dogs may represent metastatic disease or primary lung tumors, and accurate characterization of their distribution and radiodensity can inform diagnosis and management.